Water mites of the genus Monatractides (Acari: Hydrachnidia, Torrenticolidae) from Australia, with descriptions of four new species - Pešić, Vladimir; Smit, Harry (Zootaxa, 2012)
New records of water mites of the genus Monatractides (Acari: Hydrachnidia, Torrenticolidae) from streams in Australiaare presented. Four new species are described: Monatractides polypapillatus, M. ironicus, M. harveyi and M. fontinalis.A first description of the female is given for M. australicus (Cook, 1986). A key to the species of Monatractides from Australia is presented.